2013
DOI: 10.1074/mcp.m112.020552
|View full text |Cite
|
Sign up to set email alerts
|

Human Sperm Tail Proteome Suggests New Endogenous Metabolic Pathways

Abstract: Proteomic studies are contributing greatly to our understanding of the sperm cell, and more detailed descriptions are expected to clarify additional cellular and molecular sperm attributes. The aim of this study was to characterize the subcellular proteome of the human sperm tail and, hopefully, identify less concentrated proteins (not found in whole cell proteome studies). Specifically, we were interested in characterizing the sperm metabolic proteome and gaining new insights into the sperm metabolism issue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(204 citation statements)
references
References 95 publications
9
177
0
1
Order By: Relevance
“…In their recent proteomic studies of sperm, Baker et al (2013) and Amaral et al(2013) identified the proteins belonging to normal sperm head and tail domains [14,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their recent proteomic studies of sperm, Baker et al (2013) and Amaral et al(2013) identified the proteins belonging to normal sperm head and tail domains [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…The strong correlation between progressively motile spermatozoa and IVF success rates is well-proven [13]. A recent study on human sperm proteome demonstrated that some proteins of sperm tail could potentially contribute to embryo quality [14].…”
Section: Introductionmentioning
confidence: 99%
“…Triacylglycerols are a source of fatty acids, which are also important for sperm metabolism [70,71]. Amaral et al [72] have shown the association between the inhibition of a variety of enzymes involved with fatty acid beta oxidation and decreased human sperm motility, demonstrating its importance to sperm motility. In our study, the conserved protein Glyceraldehyde-3-Phosphate Dehydrogenase, testis-specific (GAPDHS), a glycolytic enzyme of the fibrous sheath involved with sperm motility [73], was involved with this function, in addition to spermatid development.…”
Section: Conserved Functionsmentioning
confidence: 99%
“…The identification of the metabolites and proteins as main determinants of the expression of the genomes and transcriptomes as also influenced by environmental cues, represents a first step to understand the normal composition and physiology of cells and tissues and their dysfunction associated with pathological states (Jodar et al, 2012;Wishart et al, 2013;Castillo et al, 2014a,b). In the case of the human spermatozoon, over 6000 proteins have been identified using mass spectrometry (MS), representing about 80% of the estimated proteome of this cell (Oliva et al, , 2009Amaral et al, 2013Amaral et al, , 2014aBaker et al, 2013;Azpiazu et al, 2014). However, and in *Correction added on 26 May 2015, after first online publication: article title corrected.…”
Section: Introductionmentioning
confidence: 99%